The Relationship Knowledge And Experience Of Sexually Transmitted Disease Infection In Female Sex Workers With Practice Condom Use - Sang Ayu Made Sri Purnami; Ni Wayan Ariyani; Ni Wayan Armini (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2018)
Sexually transmitted diseases is a diseases that transmitted through sexual intercourse. High-risk group of sexually transmitted diseases are female sex workers who did not use condoms consistently. This study aims to analyze the relationship between knowledge and experience of sexually transmitted disease infections in female sex workers with practice condom use atPuskesmas IIDenpasar Selatan. The design of this study is observational analityc with cross sectional approach.. The study period 1 to 18 December 2013. Measurement of each variable using interview guides research on 50 respondents. The results showed 54% had good knowledge,have experience of sexually transmitted disease infections 76% and only 34% of respondents use condoms consistently. There is a significant relationship between knowledge and practice in the use of condoms which p value based on chi-square was 0.000. There isn’t relationship between the experience of sexually transmitted infections by using condoms practice which is based on Fisher 's exact p value was 0.07. I recommend to increase the knowledge of female sex workers with regular education. Also recommend to develop research to analyze other factors that affect the practice of Female Sex Workers in using condoms by using a larger sample.